Antibacterial activity of the dregs of green tea leaves (Camellia sinensis L.) on Staphylococcus epidermidis as causes of acne - Naniek Widyaningrum; Badie'ah Badie'ah; Sri Lestari (Journal of Science and Science Education, 2017)
The dregs of green tea leaves have not been used until today, it is still considered as a waste that is not useful. It is known that the dregs of the green tea leaves contain Epigallocatechin-3-gallate (EGCG), which is quite high. EGCG has benefits as an antibacterial. The long-term goal of this research is the application of cosmetic preparation products from the dregs of green tea leaves that have effectiveness, stability and high economic value. The specific target of this research is to get the dose and concentration of the dregs of green tea leaves in a stable and effective way as anti-acne against Staphylococcus epidermidis (S. epidermidis). The search of the dregs of green tea leaves is by techniques of infundation of liquid fractions with ethyl acetate, identification of EGCG compound by using HPLC, antibiotics test against S. epidermidis was conducted by diffusion method. The results showed that the content of EGCG of the dregs of green tea leaves was 21.325% w/w, and the concentration of 1% of the dregs of green tea leaves can inhibit the growth of S. epidermidis well.